Studi Kompetensi Guru Nonlinier di Sekolah Menengah Atas - Neni Handayani; Risma Delima Harahap; Islamiani Safitri (Jurnal Pendidikan Edutama, 2023)
Abstract: Education is very important for human life. Without education, humans cannot know the nature of life itself. This research aims to determine how far the relationship between linear teachers and nonlinear teachers has on learning achievement. This research uses a qualitative descriptive approach. The subjects of this research were nonlinear teachers at Muhammadiyah 59 Private Middle School, Panai Hulu District, Independent Private Vocational High School, Panai Hulu District, and Karya Tani Private High School. Data collection techniques were carried out using interview techniques, while data analysis was carried out using descriptive methods. The results of this research indicate that some nonlinear teachers experience difficulties such as teaching difficulties, teaching constraints, comfort during learning, and also the learning system. Keywords: nonlinear teacher, Education, learning achievement  Abstrak: Pendidikan sangatlah penting bagi kehidupan manusia. Tanpa adanya pendidikan manusia tidak dapat mengetahui hakikat kehidupan itu sendiri. Penelitian ini bertujuan untuk mengetahui seberapa jauh hubungan antara guru linier dan guru nonlinier terhadap prestasi belajar. Penelitihan ini menggunakan pendekatan deskritif kualitatif. Subjek penelitian ini adalah guru nonlinier di SMP Swasta Muhammadiyah 59 Kecamatan Panai Hulu, SMKa Swasta Mandiri Kecamatan Panai Hulu dan SMA Swasta Karya Tani. Teknik pengambilan data dilakukan dengan teknik wawancara, sedangkan analisis data dilakukan dengan metode deskriptif. Hasil penelitian ini menunjukan beberapa guru nonlinier mengalami kesulitan seperti kesulitan mengajar, kendala mengajar, kenyamanan saat pembelajaran, dan juga sistem pembelajaran. Kata Kunci: guru nonlinier, Pendidikan, prestasi belajar